2017
DOI: 10.1186/s13068-017-0736-x
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking lichens: incorporation of yeast strains together with sucrose-secreting cyanobacteria improves survival, growth, ROS removal, and lipid production in a stable mutualistic co-culture production platform

Abstract: BackgroundThe feasibility of heterotrophic–phototrophic symbioses was tested via pairing of yeast strains Cryptococcus curvatus, Rhodotorula glutinis, or Saccharomyces cerevisiae with a sucrose-secreting cyanobacterium Synechococcus elongatus.ResultsThe phototroph S. elongatus showed no growth in standard BG-11 medium with yeast extract, but grew well in BG-11 medium alone or supplemented with yeast nitrogen base without amino acids (YNB w/o aa). Among three yeast species, C. curvatus and R. glutinis adapted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
83
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 49 publications
7
83
5
Order By: Relevance
“…However, in their process, the medium was also supplemented with ammonium salts and buffer [9]. The same seems to be true for oleaginous yeast as described by Li et al [17]. As outlined above, supplementation of the medium with additives was not necessary with P. putida cscAB as co-cultivation partner.…”
Section: Resultsmentioning
confidence: 99%
“…However, in their process, the medium was also supplemented with ammonium salts and buffer [9]. The same seems to be true for oleaginous yeast as described by Li et al [17]. As outlined above, supplementation of the medium with additives was not necessary with P. putida cscAB as co-cultivation partner.…”
Section: Resultsmentioning
confidence: 99%
“…Recent reports have shown that S. elongatus CscB can be paired with a variety of heterotrophic microbes, including Escherichia coli and Bacillus subtili s (Hays et al , ), Azotobacter vinelandii (Smith and Francis, , ), Halomonas boliviensis (Weiss et al , ), Pseudomonas putida (Löwe et al , ), Saccharomyces cerevisiae (Ducat et al , ) and Cryptococcus curvatus and Rhodotorula glutinis (Li et al , ). Such co‐cultures are typically stable over long time periods (weeks to months) and the heterotrophic partner strain can be programmed to output value‐added biological products, such as α‐amylase (Hays et al , ), fatty acids (Li et al , ) and polyhydroxyalkanoates (PHAs) [e.g. poly(3‐hydroxybutyrate) (Smith and Francis, ; Smith and Francis, ; Weiss et al , ; Löwe et al , ,b)].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we expanded upon prior efforts of engineering synthetic cyanobacteria/heterotroph consortia (Hays and Ducat, ; Smith and Francis, , ; Hays et al , ; Weiss et al , ; Li et al , ; Löwe et al , ) with the goal of generating co‐cultures that can utilize contaminated water supplies and perform a bioremediation function while also producing a valuable bioproduct from light and CO 2 (Fig. ).…”
Section: Introductionmentioning
confidence: 99%
“…In one study utilizing this engineered strain of Synechococcus elongatus PCC7942 67 (hereafter, S. elongatus CscB), sucrose secretion was such that hypothetical scaled 68 production would significantly exceed current productivities of traditional sugar crops like 69 sugar cane, sugar beet, and corn (13). As such, the strain has been utilized on numerous 70 occasions as a photosynthetic module in synthetic co-cultures as a supplier of fixed carbon 71 for heterotrophic partners (16)(17)(18)(19)(20), including a recent report where co-cultures were 72 maintained for longer than 5 months of continuous co-culture (21). Communally, these 73 works have demonstrated that the S. elongatus CscB strain can be flexibly paired with a 74 variety of heterotrophic bacteria [Escherichia coli W (16), Bacillus subtilis (16), Azotobacter 75 vinelandii (18,19), Halomonas boliviensis (21), and Pseudomonas putida (17)] and yeasts 76 [Saccharomyces cerevisiae (13,16), Cryptococcus curvatus (20), and Rhodotorula glutinis 77 (20)] and demonstrated that these co-cultures can be used to photosynthetically produce 78 valued biological products, e.g., α-amylase (16), fatty acids (20), and 79 polyhydroxyalkanoates (PHA) [e.g., poly(3-hydroxybutyrate) (PHB) (17)(18)(19)21)].…”
mentioning
confidence: 99%
“…As such, the strain has been utilized on numerous 70 occasions as a photosynthetic module in synthetic co-cultures as a supplier of fixed carbon 71 for heterotrophic partners (16)(17)(18)(19)(20), including a recent report where co-cultures were 72 maintained for longer than 5 months of continuous co-culture (21). Communally, these 73 works have demonstrated that the S. elongatus CscB strain can be flexibly paired with a 74 variety of heterotrophic bacteria [Escherichia coli W (16), Bacillus subtilis (16), Azotobacter 75 vinelandii (18,19), Halomonas boliviensis (21), and Pseudomonas putida (17)] and yeasts 76 [Saccharomyces cerevisiae (13,16), Cryptococcus curvatus (20), and Rhodotorula glutinis 77 (20)] and demonstrated that these co-cultures can be used to photosynthetically produce 78 valued biological products, e.g., α-amylase (16), fatty acids (20), and 79 polyhydroxyalkanoates (PHA) [e.g., poly(3-hydroxybutyrate) (PHB) (17)(18)(19)21)]. In work 80 from Smith and Francis (19) as well as our lab (21) it was shown that S. elongatus CscB 81 could be immobilized within hydrogels; this both enhanced carbon flux into sucrose 82 production and allowed the cyanobacteria to exchange diffusible metabolites in medium, 83 while enabling the heterotrophic cells to be readily harvested separately.…”
mentioning
confidence: 99%